Analysis of post operative complications following total thyroidectomy. - Atiq, MT; Joarder, AH; Alam, MM; Hossain, MA; Biswas, SS (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 238-44. The abstract of this article is available on the PubMed website